2001
DOI: 10.1073/pnas.161479898
|View full text |Cite
|
Sign up to set email alerts
|

An inherited p53 mutation that contributes in a tissue-specific manner to pediatric adrenal cortical carcinoma

Abstract: The incidence of pediatric adrenal cortical carcinoma (ACC) in southern Brazil is 10 -15 times higher than that of pediatric ACC worldwide. Because childhood ACC is associated with Li-Fraumeni syndrome, we examined the cancer history and p53 status of 36 Brazilian patients and their families. Remarkably, 35 of 36 patients had an identical germ-line point mutation of p53 encoding an R337H amino acid substitution. Differences within intragenic polymorphic markers demonstrated that at least some mutant alleles ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
385
1
45

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 494 publications
(455 citation statements)
references
References 36 publications
14
385
1
45
Order By: Relevance
“…Additionally, the estimated penetrance of the mutant allele was approximately 10% (Figueiredo et al, 2006;Wasserman et al, 2012). Although the mutation was found in nearly 100% of cases of ACT (Ribeiro et al, 2001), its frequency in the general population outside South and Southeast Brazil was low (Pianovski et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the estimated penetrance of the mutant allele was approximately 10% (Figueiredo et al, 2006;Wasserman et al, 2012). Although the mutation was found in nearly 100% of cases of ACT (Ribeiro et al, 2001), its frequency in the general population outside South and Southeast Brazil was low (Pianovski et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This process was found to be enhanced for the " hot-spot" R248Q contact and structural mutant, which is one of many changes in this domain known to destabilize the native structure (47). The other is for the R337H mutation in the tetramerization domain (48,49), which is associated with adrenocortical carcinoma (ACC) in children from southern Brazil (50). Both the WT and mutant peptides formed amyloid-like fibrils when incubated at pH 4.0 and elevated temperatures, with the mutant being susceptible at a lower temperature.…”
Section: Discussionmentioning
confidence: 99%
“…12 From 1996 to 1999 a subset of 92 children with ACC treated at a single institution in southern Brazil underwent genotyping of p53 and were found to have an identical point mutation in exon 10 encoding an arginine-to-histidine amino acid substitution at codon 337 of p53. 24 Although half of first-degree and a third of second-degree relatives had a similar point mutation, there was no family history of cancers to suggest Li-Fraumeni syndrome. 11 Functional studies of the protein derived from the mutated p53 gene revealed that p53 in these patients had normal activity except at high pH, which can be found in the adrenal cortex in its physiologic state, a finding that partially explained the tissue-specific cancer predisposition.…”
Section: Adrenocortical Carcinoma and Retinoblastoma As Models Of Thementioning
confidence: 99%